The Influence of Trap and Refugia Plants on Populations and Attacks of Leaf-Miner Flies Liriomyza sp. on Shallots Cultivation - Setiawati, Lia; Mudjiono, Gatot; Widjayanti, Tita (University of Brawijaya, 2023)
Leaf miners (Liriomyza sp.) are one of the pests affecting shallot plants. Attacks by Liriomyza sp. on shallot plants lead to tuber rot and leaves drying out, resembling burn damage. One control method is to utilize trap plants and refugia. Trap plants are specific species that attract pests, diverting them from the main crop. Refugia, on the other hand, are areas where pests can seek shelter, reducing their impact on the main crop. This study aimed to assess the impact of trap plants and refugia on the population and attacks of Liriomyza sp. in shallot crops. The research was conducted from June to September 2021 at the experimental field of the Faculty of Agriculture in Jatimulyo Village, Lowokwaru District, Malang City, East Java. Observation parameters included the population of Liriomyza sp., damage intensity, population of natural enemies, plant height, and number of leaves. The results indicated that different types of trap plants significantly influenced the population of Liriomyza sp. and damage intensity compared to the control treatment. However, different trap plant types did not significantly affect the population of natural enemies. The natural enemies identified included Vespidae, Coenosia sp., and Opius sp. Additionally, various trap plant types did not significantly impact plant height and the number of leaves.